Effect of Solvent Differences on Flavonoid Levels and Antioxidant Activity of Hass Avocado Peel (Persea Americana Hass) - Mery Napitupulu; Nurhikma Nurhikma; Daud K. Walanda; Detris Poba (Jurnal Akademika Kimia, 2025)
The Hass avocado fruit (Persea Americana Hass) comes from Australia. The color of the Hass avocado skin when it is still raw is green, and when it is ripe, it is black. This study aims to see the effect of different solvents in determining the levels of flavonoids and the antioxidant activity of Hass avocado peel extract. Determination of flavonoid levels using UV-Vis spectrophotometry and for antioxidant activity using 2,2-diphenyl-1-pikrihydrazyl (DPPH) as a source of free radicals, and vitamin C as a positive control, and UV-Vis spectrophotometry to measure the absorbance of Hass avocado peel extract. The results showed that the flavonoid content in the ethanol extract of avocado peel was 2.078 mg/100 mg extract, and for the methanol extract of Hass avocado peel was 1.995 mg/100 mg extract. For the antioxidant activity test, the IC50 value of the ethanol extract of avocado peel was 134.181 mg/L, while the IC50 value of vitamin C was 19.815 mg/L. For the methanol extract of Hass avocado rind, the IC50 value was 149.611 mg/L, while for vitamin C, the IC50 value was 37.093 mg/L. Ethanol extract and methanol extract of Hass avocado peel (Persea Americana hass) are classified as moderately strong antioxidants based on IC50 values.